“Because Boys Don’t Do Ballet”: Boys, Femmephobia, and the Potentials of a Femininity-Affirmative Pedagogy in Kindergarten - Prioletta, Jessica; Davies, Adam (Journal of Childhood Studies, 2024)
In this article, the authors draw on feminist theorizations to examine ethnographic data, illustrating how femmephobia is enacted among boys in kindergarten. They also examine how teachers’ well-intended responses may inadvertently legitimize femmephobia when a femininity-affirmative orientation is not applied. The authors argue that intentional gender-affirming actions by education stakeholders are necessary for promoting and supporting fluid gender explorations in kindergarten, especially in terms of valuing and validating femininity among boys. Specifically, they consider the potentials of femininity-affirmative pedagogy as one approach to countering femmephobia and working towards gender inclusion and equality in early education.